1997
DOI: 10.1192/bjp.170.6.549
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Citalopram in panic disorder

Abstract: The most advantageous benefit/risk ratio for the treatment of PD was associated with citalopram 20 or 30 mg/day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(85 citation statements)
references
References 16 publications
3
78
1
1
Order By: Relevance
“…Á Citalopram was effective in a placebo-and comparator-controlled trial (Wade et al 1997) and one comparison with fluoxetine (Amore et al 1999b). In a relapse prevention study over 52 weeks, it was superior to placebo and as effective as the TCA clomipramine (Lepola et al 1998).…”
Section: Panic Disorder and Agoraphobiamentioning
confidence: 92%
See 1 more Smart Citation
“…Á Citalopram was effective in a placebo-and comparator-controlled trial (Wade et al 1997) and one comparison with fluoxetine (Amore et al 1999b). In a relapse prevention study over 52 weeks, it was superior to placebo and as effective as the TCA clomipramine (Lepola et al 1998).…”
Section: Panic Disorder and Agoraphobiamentioning
confidence: 92%
“…In a 26-week long-term study, it was as effective as fluoxetine (Amore et al 1999a) (A). Á Clomipramine also showed efficacy in DBPC Johnston et al 1988) and comparator-controlled studies (Cassano et al 1988;Fahy et al 1992;Modigh et al 1992;Wade et al 1997).…”
Section: Tricyclic Antidepressants (Tcas) Treatment Withmentioning
confidence: 99%
“…Within the TCAs, both imipramine and clomipramine have been studied (Cross National Collaborative Panic Study, Second Phase Investigators, 1992;Papp et al, 1997). The currently available SSRIs citalopram, escitalopram, fluvoxamine, fluoxetine, paroxetine, and sertraline have all been proven more effective than pill-placebo in reducing symptomatology in PD (Ballenger et al, 1998a;Black et al, 1993;Hoehn-Saric et al, 1993;Lecrubier et al, 1997;Michelson et al, 1998;Rapaport et al, 1998;Sharp et al, 1996;Wade et al, 1997). The daily dosages of these antidepressants are similar to those used in the treatment of major depressive disorder (see Table 1).…”
Section: Pharmacotherapy Of Pdmentioning
confidence: 99%
“…Relatively few studies have compared different antidepressants in PD (Bakker et al, 1999;Cassano et al, 1988;den Boer et al, 1987 ;den Boer and Westenberg, 1988;Lecrubier et al, 1997;Modigh et al, 1992;Nair et al, 1996;Seedat et al, 2003 ;Tiller et al, 1997;Wade et al, 1997). In most studies, different antidepressants have shown equal efficacy in reducing the total number of panic attacks.…”
Section: Tcas Vs Ssrismentioning
confidence: 99%
See 1 more Smart Citation